Utilization of Karangsong Beach as a Learning Resources Based on Local Wisdom in Improving Understanding of the Concept Students of Primary Teacher Education - Kiki Fatkhiyani; Dadang Suhada (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2018)
This research was conducted to improve the understanding of the concept of PGSD students STKIP NU Indramayu by utilizing the Karangsong beach as a learning resource based on local wisdom. The research method used is mixed method research or sequential explanatory strategy, which is a strategy that is applied by collecting and analyzing quantitative data in the first stage. In this study, data collection and analysis increase understanding of the concept of living things and their environment after being treated, followed by collecting and analyzing qualitative data in the second stage, namely revealing obstacles and solutions to students in utilizing the Karangsong beach as a learning resource based on local wisdom. The research subjects were PGSD students at STKIP NU Indramayu who attended the basic concepts of biology in elementary school. The utilization of Karangsong beach as a learning resource based on local wisdom can improve students' understanding of concepts as evidenced by the acquisition of  N-Gain values of 0.81 in the high category. As for the constraints and obstacles faced by students revealed through interviews. Based on the results of interviews, external factors are more than internal factors. The lack of application of the right learning model is one of the inhibiting factors in this study. This has caused learning goals cannot be achieved optimally